2019
DOI: 10.1080/08998280.2019.1608623
|View full text |Cite
|
Sign up to set email alerts
|

Not-so-benign massive cardiac lipoma

Abstract: Cardiac lipomas are rare and usually benign tumors that often remain asymptomatic throughout one's lifetime. We report a case of a 60-year-old man with a cardiac lipoma diagnosed early in childhood. However, due to the lack of surgical expertise in rural India, the lipoma was not removed. After moving to the United States, he received irregular follow-up with serial chest x-ray and computed tomography, which demonstrated an enlarging lipomatous mass occupying the pericardial space. After remaining asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…Although most of them show an indolent nature [ 32 ], aggressive growth, including infiltration into the myocardium, has been reported. Cardiac lipomas may grow to a very large size and infiltrate the myocardium deeply [ 33 , 34 ]. In some cases, they are even capable of melting the myocardium and developing cavities in the lipomas that communicate with cardiac chambers, thus having a pseudoaneurysmal appearance [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most of them show an indolent nature [ 32 ], aggressive growth, including infiltration into the myocardium, has been reported. Cardiac lipomas may grow to a very large size and infiltrate the myocardium deeply [ 33 , 34 ]. In some cases, they are even capable of melting the myocardium and developing cavities in the lipomas that communicate with cardiac chambers, thus having a pseudoaneurysmal appearance [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more frequent follow-up in patient 12 in the present study prompted the earlier discovery of recurrence and a chance to remove the lipoma without transplantation. Patients initially not considered for surgery should be closely followed up using imaging methods because potential infiltrative growth into the myocardium may result in failed resection in the future [ 33 ]. On the contrary, despite no evidence that cardiac lipoma might undergo malignant transformation, mature lipomas and well-differentiated liposarcomas coexist in one heart.…”
Section: Discussionmentioning
confidence: 99%
“…Interatrial lipomatous hypertrophy found in the pathological differential diagnosis is a rarely observed non-capsular hamartomatous lesion and is also called as lipomatous hypertrophy of the atrial septum. Even though the resection of cardiac lipomas is mostly easily performed, a small number of patients with extensive spread, unfortunately, undergo a difficult surgery, having poor outcomes [ 17 ] . The case of lipoma in our series was successfully resected, and no complication developed.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of them show an indolent nature 31 , aggressive growth, including in ltration into the myocardium, has been reported. Cardiac lipomas may grow to a very large size and in ltrate the myocardium deeply 32,33 . In some cases, they are even capable of melting the myocardium and developing cavities in the lipomas that communicate with cardiac chambers, thus having a pseudoaneurysmal appearance 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…A more frequent follow-up in patient 12 in the present study prompted the earlier discovery of recurrence and a chance to remove the lipoma without transplantation. Patients initially not considered for surgery should be closely followed up using imaging methods because potential in ltrative growth into the myocardium may result in failed resection in the future 32 . On the contrary, despite no evidence that cardiac lipoma might undergo malignant transformation, mature lipomas and well-differentiated liposarcomas coexist in one heart.…”
Section: Discussionmentioning
confidence: 99%